An Empirical Study on the Quality of Industry-Linked Education in Vocational Colleges: Double-Framed TreeSoft Set Framework - Yanbin Liu; Peina Liang; Jingjie Ma (Neutrosophic Sets and Systems)
Integrating industry-linked education into vocational college courses has been a key tactic for improving workforce preparedness in recent years. This study examines the extent and efficacy of industrial cooperation in vocational education contexts, emphasizing the effects of such alliances on innovation, employability, and skill acquisition. The study identifies obstacles that must be overcome and emphasizes important elements that lead to effective integration through empirical investigation. This study uses the multi-criteria decision making (MCDM) to deal with criteria and alternatives. The MAIRCA method is used to rank the alternatives. We use the Double-Framed TreeSoft Set to divide the main criteria into a tree. The findings are intended to provide useful information to industry partners, educators, and legislators who are trying to improve the caliber of vocational education.